Physical Match Demands of International Women’s Rugby Union: A Three-Year Longitudinal Analysis of a Team Competing in The Women’s Six Nations Championship - David Nolan; Orlaith Curran; Aidan J. Brady; Brendan Egan (Journal of Functional Morphology and Kinesiology, 2023)
There is a paucity of studies describing the physical match demands of elite international women’s rugby union, which limits coaches’ ability to effectively prepare players for the physical demands required to compete at the elite level. Global positioning system technologies were used to measure the physical match demands of 53 international female rugby union players during three consecutive Women’s Six Nations Championships (2020–2022), resulting in 260 individual match performances. Mixed-linear modelling was used to investigate differences in physical match demands between positions. Significant effects (p < 0.05) of the position were observed for all variables, with the exception of relative distances (m.min−1) at velocities of 1.01–3.00 m·s−1 (p = 0.094) and 3.01–5.00 m·s−1 (p = 0.216). This study provides valuable data on the physical match demands of elite international women’s rugby union match play that may aid practitioners in the physical preparation of players to compete at this level. Training methodologies for elite-level female rugby union players should consider the unique demands across positional groups with specific considerations of high-velocity running and collision frequency.